A tendency to worse course of multisystem inflammatory syndrome in children with obesity: MultiOrgan Inflammatory Syndromes COVID-19 related study - Gawlik, Aneta Monika; Berdej-Szczot, Elżbieta; Chmiel, Iga; Lorek, Miłosz; Antosz, Aleksandra; Firek-Pędras, Małgorzata; Szydłowski, Lesław; Ludwikowska, Kamila Maria; Okarska-Napierała, Magdalena; Dudek, Natalia; Piwoński, Krzysztof; Afelt, Aneta; et al. (Frontiers in Endocrinology, 2022)
Background: The new entity called Multisystem Inflammatory Syndrome in Children (MIS-C) is a rare consequence of COVID-19 infection. The pathophysiology and risk factors of MIS-C are not yet clear, and the clinical manifestation ranges from milder forms to cases needing intensive care unit treatment. Based on available data, obesity is linked with pro-inflammatory stimulation. Moreover, several studies showed that obesity could play a role in COVID-19 severity and its comorbidities among the adult and children population. Aim: To investigate the influence of overweight/obesity in childhood for the course of MIS-C in Poland. Methods: The study presents data from the national MultiOrgan Inflamatory Syndromes CoVID-19 Relates Study (MOIS-CoR) collected between 4th March 2020 and 20th February 2021. Of 371 patients fulfilled Polish MIS-C criteria, 306 were included into further analysis. Results: Children with obesity (OB/BMI=or>95pc) and overweight (OV/BMI = or>85 pc but <95pc) (28 and 49, respectively) represented 25.1% (n=77) of all recruited patients. Complete recovery at the moment of discharge presented 93% of normal body weight (NW) participants and 90 % of those with BMI at least 85 pc (p>0.05). Of OB children 76% recovered fully and differed from the NW group (p=0.01). Calculated OR of incomplete recovery for OB children was 4.2. Irrespective of body weight there were no differences (p>0.05) in the length of hospitalization and the duration of symptoms (for OB 13 and 16.5, for OV & NW 10 and 14 days, respectively), as well as in the frequency of cardiovascular abnormalities, necessity of oxygen therapy (OB 26.9%, OV 23.9%, NW 20.7%), intravenous immunoglobulins and glucocorticosteroids treatment. Conclusions: The higher risk of incomplete recovery and observed tendency to worse course of MIS-C in patients with obesity suggest the need for further studies to confirm and understand our findings.